Analisis Kualitatif Metabolit Sekunder dan Aktivitas Antioksidan Jamur Endofit Cangkang Bulu Babi (Diadema setosum) - Widy Susanti Abdulkadir; Mahdalena Sy. Pakaya; Fika Nuzul Ramadhani; Wiwit Zuriyati Uno; Arona Salama (Jurusan Farmasi Universitas Negeri Gorontalo, 2023)
Endophytic fungi are fungi that live in plant tissues for a certain period and can form colonies in the host's tissues without endangering the host itself. In addition to plants, endophytic fungi are also found in marine biota. Endophytic fungi that live in the internal organs or tissues of marine biota, whether in the form of mold or yeast, can transform the nutrients they obtain from their host animals into metabolite compounds which will then be transferred back to the host organs so that they have the same metabolites as their hosts. This study aimed to analyze and test the antioxidant activity of the secondary metabolites of sea urchins in the Tomini Bay area. The method used from the beginning of the research was endophytic microbial fermentation, production of secondary metabolites, and partitioning of endophytic microbial isolates, namely liquid-liquid; the method used to test antioxidant activity was qualitative using TLC plates, DPPH UV-Vis spectrophotometer method, color reagent, and thin layer chromatography. Two isolates of endophytic fungi were obtained, namely (JBB1, JBB2). The isolate that was active as an antioxidant was JBB2 from sea urchins in the Tomini Bay area with an ICso 50-100 ppm, which was in the strong category. Meanwhile, JBB2 isolate was carried out at a wavelength of 517 nm with a value absorbance of 0,707 A. In accordance with the value of the linear equation, it obtained y = 0,092x+36,95 and an R2 value = 0,945 that the ethyl acetate extract in JBB2 had a moderate ICs of 87.43 µg/mL. Meanwhile, the qualitative test of secondary metabolites using thin layer chromatography with n-hexane eluent: ethyl acetate (8:2) ethyl acetate extract contained alkaloid and terpenoid compounds.